The Authority of the Village Consultative Body in Determining Village Development Policies Based on Law Number 6 of 2014 Concerning Villages - Rifai, Muhamad; Burlian, Paisol; Yazwardi, Yazwardi (Jurnal Mediasas: Media Ilmu Syari'ah dan Ahwal Al-Syakhsiyyah, 2025)
This study examines the authority of the Village Consultative Body (BPD) in determining the direction of village development policies as regulated in Law Number 6 of 2014 concerning Villages. As a village legislative institution, the BPD holds a strategic role not only as a supervisory body but also as a partner to the Village Head in formulating, deliberating, and approving development policies that directly affect community welfare. This research employs a normative juridical method with statutory, historical, and case approaches to analyze the relationship between legal norms and the practical implementation of village governance. The findings indicate that the implementation of BPD’s authority remains suboptimal due to limited human resource capacity, weak communication with village governments, and low community participation in development planning. Therefore, institutional strengthening, continuous capacity building for BPD members, and enhanced synergy with village governments are necessary to establish democratic, participatory, and accountable village governance. [Penelitian ini membahas kewenangan Badan Permusyawaratan Desa (BPD) dalam menentukan arah kebijakan pembangunan desa sebagaimana diatur dalam Undang-Undang Nomor 6 Tahun 2014 tentang Desa. Sebagai lembaga legislatif desa, BPD memiliki peran strategis tidak hanya sebagai pengawas, tetapi juga mitra Kepala Desa dalam merumuskan, membahas, dan menyepakati kebijakan pembangunan yang berdampak langsung pada kesejahteraan masyarakat. Penelitian ini menggunakan metode yuridis-normatif dengan pendekatan perundang-undangan, historis, dan kasus untuk menganalisis keterkaitan antara norma hukum dan praktik penyelenggaraan pemerintahan desa. Hasil penelitian menunjukkan bahwa pelaksanaan kewenangan BPD belum optimal karena keterbatasan kapasitas sumber daya manusia, lemahnya komunikasi dengan pemerintah desa, serta minimnya partisipasi masyarakat dalam proses perencanaan pembangunan. Untuk itu, diperlukan strategi penguatan kelembagaan, pelatihan berkelanjutan bagi anggota BPD, serta sinergi yang lebih baik dengan pemerintah desa guna mewujudkan tata kelola pemerintahan desa yang demokratis, partisipatif, dan akuntabel.]